PENGGUNAAN MEDIA DIORAMA UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN TENTANG DENAH TEMPAT TINGGALKU KELAS III SD INPRES OEBA 1 - bully, wike; Koro, Maxsel; Ratu, Kurniayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine whether the use of diorama media can improve students' learning outcomes on the material "My Residence Plan" in grade III of elementary school. The focus of this study was to evaluate students' understanding through the use of diorama media. The type of research used was Classroom Action Research (CAR) which was conducted in two cycles with stages of planning, implementation, observation/testing, and reflection. The subjects of the study consisted of 20 grade III students, with data obtained through observation and testing, which were analyzed descriptively and quantitatively. The results showed that in cycle I, the level of student learning completion only reached 45% (9 students), while 55% (11 students) had not met the Learning Objective Completion Criteria (KKTP). After improvements were made in cycle II, there was a significant increase, with learning completion reaching 80% (16 students) and 20% (4 students) declared incomplete. Thus, it can be concluded that the use of diorama media improves students' learning outcomes on the material.